The sarcoma ring trial: a case-based analysis of inter-center agreement across 21 German-speaking sarcoma centers - Siyer Roohani; Jolina Handtke; Kamal Hummedah; Markus Albertsmeier; Dimosthenis Andreou; Leonidas Apostolidis; Marinela Augustin; Sebastian Bauer; Moritz Billner; Florian Bösch; Christoph K. W. Deinzer; Niklas Deventer; et al. (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose The management of soft tissue sarcoma (STS) at reference centers with specialized multidisciplinary tumor boards (MTB) improves patient survival. The German Cancer Society (DKG) certifies sarcoma centers in German-speaking countries, promoting high standards of care. This study investigated the variability in treatment recommendations for localized STS across different German-speaking tertiary sarcoma centers. Methods In this cross-sectional case-based survey study, 5 anonymized patient cases with imaging data of localized STS were presented to MTBs of 21 German-speaking tertiary referral hospitals. Centers provided recommendations on treatment sequence and modalities, along with the consensus level within their MTB. Agreement percentages were calculated, and consensus levels were rated on a scale of 1 to 10. Results Five patient cases were discussed resulting in 105 recommendations. Agreement percentages for case 1 to 5 were 14.3%, 61.9%, 33.3%, 52.4% and 9.3%, with a median agreement percentage of 33.3%. Grouping pre- and postoperative therapies as "perioperative" and including recommendations with and without regional hyperthermia raised the median agreement to 47.6%. The mean consensus level within each center across all 5 cases was 9.5. Conclusion This first case-based analysis of inter-center agreement for STS management in German-speaking countries reveals low inter-center agreement but high intra-center consensus. Our study includes nearly all tertiary sarcoma centers in German-speaking countries, affirming its strong external validity. These findings suggest potential and clinically very relevant differences in treatment standards among sarcoma centers. Enhanced case-based exchanges and collaborative efforts are needed to reduce discrepancies and standardize the management of STS patients.